Taking from the disadvantaged? Consumption tax induced poverty across household types in 11 OECD countries - Manuel Schechtl (Luxembourg Income Study (LIS), 2021)
Consumption taxes are a pivotal yet largely unaddressed policy tool that shape the income distribution and potentially thwart the redistributive goals of social policy. Previous research showed how consumption taxes can elevate inequality and poverty on the macro level. However, different household types might be affected differently due to diverging income positions and consumption needs. In this study, I aim to examine the change in income poverty across household types when accounting for consumption tax payments. To address my research interest, I draw on harmonised data from 11 OECD countries provided by the Luxembourg Income Study (LIS). I estimate implicit indirect tax rates from national accounts and investigate poverty rates of household types before and after subtracting consumption taxes. Using logistic regression models, I scrutinise the probability of falling under the poverty line due to consumption tax payments. The results indicate significant variation in poverty changes across household types. In most countries, people in large families and single parent households have a higher probability of falling under the poverty line when compared to couple households. Ultimately, results from linear probability models with country-fixed effects indicate that the consumption tax rate is positively associated with the elevation in poverty for single parents.
Keywords: 330; Verbrauchsteuer; Einkommensverteilung; Privater Haushalt; Wirkungsanalyse; OECD-Staaten